Pengaruh Mahkamah Konstitusi terhadap Stabilitas Sistem Ketatanegaraan Indonesia - Igirisa, Jeis; Usman, Nurvia; Moonti, Roy Marthen (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The Constitutional Court (MK) has a strategic role in maintaining the stability of the Indonesian constitutional system through its main function as a guardian of the constitution. This article aims to analyze the influence of the Constitutional Court on constitutional stability, both through legal testing of the 1945 Constitution, the resolution of authority disputes between state institutions, and through supervision of the implementation of elections. Using a normative juridical approach, this article reveals that the Constitutional Court has made a significant contribution in maintaining balance between state institutions, ensuring electoral justice, and upholding the supremacy of the constitution. Nevertheless, challenges such as the independence of judges and the implementation of judgments remain issues that require attention. This article recommends strategic steps to enhance the role of the Constitutional Court in strengthening the stability of Indonesia's constitutional system.